STRATEGIES FOR ENHANCING TEACHER COMPETENCE AND PROFESSIONALISM AT SMK PUTRA PELITA TENJOLAYA - Siti Adji; Iu Rusliana; Fikri Alamsyah; Nuraeni; Al-Gaisya, Annisa (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2024)
This research is motivated by the need to understand the strategies for improving the competence and professionalism of teachers at SMK Putra Pelita Tenjolaya. Teaching is a profession characterized by a certain level of professionalism. The purpose of this study is to identify strategies for enhancing teacher competence. The research employs a qualitative research method with a descriptive approach. Data collection is conducted through semi-structured interviews. The results of this study indicate that there are several ways to enhance the professionalism and competence of teachers. These include organizing continuous training and self-development programs. Additionally, teachers can collaborate with peers to enrich insights and understanding. The role of the school principal in enhancing teacher professionalism is also crucial as a form of support for the progress of teachers at SMK Putra Pelita Tenjolaya. Keywords: Utilization; Talent; Teacher; HR; Institutions.